1996
DOI: 10.5840/monist19967919
|View full text |Cite
|
Sign up to set email alerts
|

Events, Topology and Temporal Relations

Abstract: We are used to regarding actions and other events, such as Brutus' stabbing of Caesar or the sinking of the Titanic, as occupying intervals of some underlying linearly ordered temporal dimension. This attitude is so natural and compelling that one is tempted to disregard the obvious difference between time periods and actual happenings in favor of the former: events become mere "intervals cum description".1 On the other hand, in ordinary circumstances the point of talking about time is to talk about what actua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 32 publications
0
12
0
1
Order By: Relevance
“…For instance, [65] gives a version of the theory using 'IP' as a primitive; [48,49,50] give an equivalent formulation based on 'c' as a primitive and (60)- (61) as axioms. A version of the same theory based on the primitive 'boundary' is found in [51]. A slightly weaker formulation, based on 'IP', can also be found in [70], though this theory turns out to be defective in various respects.…”
Section: Definition 8 the Theory Of General Extensional Mereotopologmentioning
confidence: 98%
“…For instance, [65] gives a version of the theory using 'IP' as a primitive; [48,49,50] give an equivalent formulation based on 'c' as a primitive and (60)- (61) as axioms. A version of the same theory based on the primitive 'boundary' is found in [51]. A slightly weaker formulation, based on 'IP', can also be found in [70], though this theory turns out to be defective in various respects.…”
Section: Definition 8 the Theory Of General Extensional Mereotopologmentioning
confidence: 98%
“…In [6] we have shown that such relations can ultimately be construed from some basic ontological properties that a domain of events must arguably satisfy-specifically, mereological and topological properties. The construction is refined in [7], and in [8] it is shown to be especially liable to the sort of refinement that is requiired to account for the context-dependence exhibited by natural language. Here is a brief review of this construction.…”
Section: Event Structuresmentioning
confidence: 99%
“…In addition to the these basic mereotopological notions, the following notions are introduced in [7] with an eye to their use in characterizing event domains:…”
Section: Event Structuresmentioning
confidence: 99%
“…This becomes apparent especially in connection with qualitative reasoning about space and time: here mereology proves useful to account for certain basic relationships among things or events; but one needs topology to account, say, for the fact that two objects or events can be continuous with each other, or for the relation of something being inside, abutting, or surrounding something else. (My present concern will be with the mereotopology of spatial structures; I have explored eventive and other temporal structures in joint work with Fabio Pianesi [25,26,27]. )…”
Section: 3mentioning
confidence: 99%
“…This is the strategy favored here. Following in the footsteps of [45], the topological primitive will be a binary relation of topological connection (we could as well use the notion of boundary, or that of interior parthood: see [26,36,38,42] for some such alternatives). This relation will be denoted by 'C(x, y)' and will be read "x is connected with y".…”
Section: 3mentioning
confidence: 99%